Reviewing the Performance Of Local Governments In Managing Corporate Social Responsibility Program - Matala, Andi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
Regional governments are obliged to provide welfare for their people, either through the original regional budget, the central transfer budget, or the CSR budget of companies in their area. In Kolaka Regency, there are many mining companies. It is the company's obligation to contribute to the community through CSR funds, and the party most authorized to deal with these problems is the local government, whose funds can then be channeled to the community through community programs. This research was conducted to review how the local government of Kolaka district can collect CSR funds from companies and distribute them to the community through regional development programs, such as health, education, social, religious programs, environmental assistance and so on. This research is qualitative, case study research, and survey method. The data analysis technique used was descriptive based on SWOT analysis. The object of research is the local government of Kolaka, with correspondents consisting of local government employees, community leaders, and communities around the mine. The results of the study indicate that the local government of Kolaka is in a weak position towards the utilization of CSR opportunities. Although local governments have the power in the form of regulations to be able to demand CSR funds from companies, the fact is that the relevant agencies have not been able to collect as much CSR funds as possible to be channeled to the community in development and community welfare programs.